Effect of WCO addition on high and low-temperature performance of RET modified bitumen - Kumandas, Aytug; Cavdar, Erman; Oruc, Seref; Pancar, Erhan Burak; Kok, Baha Vural (Elsevier Sci Ltd, 2022)
Reactive Ethylene Terpolymers (RET), one of the popular additives in recent years, provide a significant improvement in the performance of bitumen. With the use of RET modified bitumen (RETMB), the workability of the mixtures decreases, and the energy requirement for pavement construction and CO2 emission increases. On the contrary, Waste cooking oils (WCO) reduce the viscosity of bitumen and increase workability. As a solution to the increased workability of RET modified binders, RET and WCO were used together in this study. In the study, 2-8 wt% WCO was added in 2% increments to the bitumen, modified with 1.5 wt% RET and 0.2 wt% polyphosphoric acid (PPA) as a catalyst. The physical, chemical, and rheological properties of the modified binders were investigated. As a result of the studies, it was observed that the WCO additive increased the workability of RETMBs and their resistance to fatigue and low-temperature cracking. Thus, it has been concluded that RET + WCO composite modified bitumen may be suitable for asphalt pavement constructions, especially in cold climates. In addition, by using this composite modification, an environmentally friendly approach may be achieved by reducing CO2 emissions during pavement construction.
Keywords: Bitumen modification; Reactive ethylene terpolymer; Waste cooking oil; Performance grade; Continuous grades